Peran Strategis Penyuluh Agama Islam dalam Menguatkan Mental dan Spiritual Keluarga Disabilitas di Family Support Group Kabupaten Wonosobo - Mustika Septi Handini (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Families with disabled members often face physical, emotional, social, and spiritual challenges. In this situation, the presence of Islamic religious instructors is essential to strengthen the mental and spiritual well-being of the family. This article aims to examine the strategic role of Islamic religious instructors in this context, an aspect that has not been widely studied before. Field research was conducted for two months, January–February 2025, at the Family Support Group in Wonosobo Regency, involving 27 respondents. The results of the study indicate that religious instructors have an important role in assisting families with disabilities. For this reason, a comprehensive and empathetic counseling strategy is needed, namely: an empathetic and conducive approach, a planned systematic approach, and a sustainable approach through networks. These three approaches are based on the principles of rahmatan lil 'alamin (compassion), wasathiyah (moderation), and participatory (involving the family as the subject). This article emphasizes the importance of the role of Islamic religious instructors, and recommends that the Ministry of Religion draft regulations that prioritize counseling services for families with disabilities.